2005
DOI: 10.1177/0894318405274829
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Lived Experience of Waiting for Persons in Long-Term Care

Abstract: The purpose of this study was to describe the meaning of waiting for persons who reside in long-term care settings. Parse's theory of human becoming provided the nursing perspective and a qualitative descriptive-exploratory design was used. The 45 participants were residents in three different long-term care facilities affiliated with a university. Data were gathered through interviews. Three emergent themes formed the following unified description: The experience of waiting is intensifying ire while diversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In the study by Naef and Bournes (2009), participants said that having the support of others helped them to wait, was encouraging, and was enlivening as personal affiliations and activities were offered while waiting. This notion was also found in a study by Mitchell and colleagues (2005) where persons described that when waiting, it was helpful in setting up patterns related to immersing oneself in various activities or thoughts and the need to engage in these activities to ease the waiting. From these findings, it may be inferred that nurses have a vital role in engaging with those who wait and enhance personal understanding by questioning and invoking what is most important to them, and how they can be helpful.…”
Section: A Humanbecoming Ethos Of Waitingmentioning
confidence: 61%
“…In the study by Naef and Bournes (2009), participants said that having the support of others helped them to wait, was encouraging, and was enlivening as personal affiliations and activities were offered while waiting. This notion was also found in a study by Mitchell and colleagues (2005) where persons described that when waiting, it was helpful in setting up patterns related to immersing oneself in various activities or thoughts and the need to engage in these activities to ease the waiting. From these findings, it may be inferred that nurses have a vital role in engaging with those who wait and enhance personal understanding by questioning and invoking what is most important to them, and how they can be helpful.…”
Section: A Humanbecoming Ethos Of Waitingmentioning
confidence: 61%
“…Transcendental phenomenology has been used to improve understanding about deeply personal experiences of ill-health such as hearing loss [27], organ transplantation [28], and chronic pain [29]. A recent study demonstrates its utility in exploring the experiences of long term care residents in care [30]. In the current study, it was imperative to allow the voices of residents to emerge undistorted by preconceptions or biases about the potential merits of heart failure care.…”
Section: Methodsmentioning
confidence: 99%
“…Mitchell and colleagues (2005) investigated the lived experience of waiting. The findings of their study suggested that when participants have to wait when the surgeon is delayed or their surgery is rescheduled, they think that they are being ignored or neglected and this disregard contributes to the anger and frustration that they experience.…”
Section: Related Literaturementioning
confidence: 99%